2021
DOI: 10.5154/r.rchsat.2021.02.05
|View full text |Cite
|
Sign up to set email alerts
|

La semilla de cachichín (Oecopetalum mexicanum Greenm. & C.H. Thomps.): Fuente de nutrimentos y compuestos bioactivos

Abstract: El cachichín (Oecopetalum mexicanum Greenm. & C.H. Thomps.) es una especie arbórea que produce una semilla comestible a la que se han atribuido propiedades nutracéuticas importantes para mejorar la salud humana. El objetivo de este trabajo fue analizar los aspectos más relevantes de investigaciones científicas en torno al cultivo, las propiedades nutritivas y potencial farmacológico de esta semilla. Se identificaron diversa fuentes literarias y bases de datos que a la fecha se han integrado sobre el cachic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The nut can be sold raw, boiled, or toasted (Lascurain et al, 2009). Some research has been carried out on the nutritional properties of these nuts, and it has been found that, on average, they contain 10 % protein, 40 % lipids, 5 % fiber, 2 % ash, and less than 1 % sugars (Hernández-Mora et al, 2021). Additionally, the nuts contain saponins, sterols, and coumarins, which are antioxidant compounds important in nutrition and human health (Hernandez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The nut can be sold raw, boiled, or toasted (Lascurain et al, 2009). Some research has been carried out on the nutritional properties of these nuts, and it has been found that, on average, they contain 10 % protein, 40 % lipids, 5 % fiber, 2 % ash, and less than 1 % sugars (Hernández-Mora et al, 2021). Additionally, the nuts contain saponins, sterols, and coumarins, which are antioxidant compounds important in nutrition and human health (Hernandez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%